Kid innovators : true tales of childhood from inventors and trailblazers - Stevenson, Robin, 1968-; Steinfeld, Allison (Philadelphia, PA : Quirk Books, 2021)
"Childhood biographies of sixteen trailblazers in technology, education, business, science, art, and entertainment"--Provided by publisher.
Includes bibliographical references (p. 196-200) and index.
6.0
3-6.
3-6
Keywords: Businesspeople -- Biography -- Juvenile literature; Inventors -- Biography -- Juvenile literature; Businesspeople; Inventors; Businesspeople -- Biography; Inventors -- Biography; Biographies